Assessing the archaeological visibility of late Holocene herders in the middle Limpopo Valley: a regional synthesis - Forssman, Tim (Southern African Humanities, 2025)
Scholars have long sought to trace the movements of herder communities arriving in southern Africa during the late Holocene. Existing models propose various routes, generally involving migration from the north through central southern Africa, as well as to the west coast before turning south. The former route passes through the middle Limpopo Valley, where herders are thought to have lived in the last two millennia. However, this possibility has not yet been fully assessed archaeologically. This paper reviews and synthesizes available data from Later Stone Age contexts, both excavated and analysed surface assemblages, to evaluate whether there is evidence for a herder presence in the region between the final centuries BC and the early 2nd millennium AD. It considers rock art, faunal, ceramic, stone tool and settlement patterns to identify variations in the Later Stone Age sequence that might signal the arrival or movement of herders through the valley. Although some regional differences are evident, their significance and whether they reflect distinct cultural groups remains uncertain. Identifying herders is not straightforward and is further complicated by how we construct cultural identities around archaeological markers, frameworks that may not reflect how people in the past understood or expressed their own identities. This paper additionally contributes to better understanding social and subsistence dynamics present in the middle Limpopo Valley during the late Holocene when several social, political and economic transformations were taking place.